Vietnam and India: A discourse on Buddhist contacts - Mishra, Patit Paban (2011)
India and Southeast Asia are two important regions of Asia. Both have played meaningful roles in history through cultural contacts and trading relationship.There have been profound changes in religion, society and economy of the regions due to trans-national migration and cross-cultural movements.The Indian cultural influence in Southeast Asia forms a fascinating aspect of India-Southeast Asia relations.The dynamics of Southeast Asian culture resulted in a meaningful pattern of diachronic interaction between India and Southeast Asia.Maritime commercial network in Asia unleashed a cultural process resulting in introduction of Buddhism into Vietnam.The discovery of items like shouldered adzes, knobbed ware, glass beads etc from different sites in India and Vietnam point to the relations between the two regions in pre-historic times.There was also commercial relationship between India and Vietnam in early times.Along the Asian sea route, trade and commerce increased during the first two centuries of Common Era.The northern Vietnam under Chinese rule became a centre of Buddhist learning, as it was a convenient halting place for pilgrims and missionaries on their journey between India and China.There was coming of Buddhist monks to Tonking region.At the end of third century, Marajivaka went from India to Tonking.In the seventh century, the Vietnamese monks such as Moksadeva, Khuy Sung and Hue Diem went on pilgrimages to different places.There were twelve Vietnamese names in the list of Buddhist scholars prepared by the Chinese traveler I. Ching.One of the important aspects of Vietnamese Buddhism was that there was no attempt to integrate Hindu Gods.It was associated with Confucianist and Taoist traditions.In the southern kingdom of Campa, there was prevalence of the closely related Theravadin sect, aryasammitiyanikaya as had been noted by I. Ching.Buddha images of Amaravati style pertaining to early centuries of Common Era have been found from Dong-duong near Danang in central Vietnam.An inscription of the same region describes the installation of a Buddha image in 875 C.E. and construction of a Buddhist temple and monastery by Indravarman II.In the present article, an attempt has been made to delineate Buddhist contacts between India and Vietnam.The article would contest the Indic centric view that there was total transplantation of Indian Buddhism.The theoretical premise would be that the whole process of Indian cultural influence was interaction between culture of India and Vietnam.It was the genius of Vietnamese, which choose those elements of an external culture that were either consistent with or could be moulded to its own beliefs.